Description Of Differences In Creative Thinking Profile For Male And Female Students In Open Ended Problem Solving - Islam, Hana Shohwatul; Budiyono, Budiyono; Siswanto, Siswanto (Universitas Sebelas Maret, 2021)
One of the manifestations of high-level thinking is creative thinking, characterized by creating something new from ideas, concepts, experiences, and knowledge that is in one's mind. This study aims to describe the creative thinking profile of male and female students in solving open-ended problems. The research method used is descriptive research with a qualitative approach. The subject of the study used was 2 grade VII students of SMP Negeri 3 Surakarta. This research instrument uses open-ended problem tests with indicators of creative thinking and interviews. In describing the student's creative thinking profile, the researcher will pay attention to 4 stages: preparation, incubation, illumination, and verification stages. The results of this study show that male students can explain problems and solutions orally or in writing. While female students can explain the problem and the solution is both verbally but less able to explain with writing